Exploring Social and Cultural Values in Contemporary Literature (Global Journal of Human-Social Science, 2020)
Paper aims to explore effect of society and cultural norms on minds of contemporary writers. Through literary writings students understand how world moves forward through interdependency. Writers writing in realistic stream try to touch upon facts and not on assumptions. They observe real life characters in a society set up and do not write what comes as historical truth. Complex behaviour can be seen in complex writings of contemporary writings. Man being a social animal loves to live life without adhering to age old traditions that gave strength to inner make up of one's character. Literature reflects negative and positive side of modern man. What is dealt with in Social Sciences, the same is pored out in words by poets, dramatists and novelists. Non literary writers like Jared Diamond emphasize upon effect of land topography on man's thinking process and not history or society that is all around him. Contemporary world is full of hardships. Examples from literary texts can support one to deal with these hardships. Examples would be taken from works written after World War 11 that fall under contemporary literature. Couple of books would be touched upon under the lens of socioeconomic, socio-political and socio-religious aspects as values take shape from all that a person undergoes and all that is around him and these are just few things that affect a personality.